До питання Приуральського джерела давньоугорського етносу - Вереш, П. (Народна творчість та етнографія, 2005)
The author of the article presents S. Tolstov's concept of Uralian origin of ancient Ugric people, the idea which played a great role in further research of ethnic history of Finno-Ugric folks. The starting point for them is considered to be Middle Asia, not far from the Aral sea. Some linguistic, ethnographic, and paleoclimatic data on the issue of ethnogeny of several Ugric folks are suggested.